Use of teacher's language style in the grade 3 learning process of Ciheuleut 1 Elementary School Bogor - Yusyifa, Yuhan (CV. Mitra Palupi, 2021)
Background: Â the communication pattern applied by the teacher becomes a vital thing to be discussed.Purpose: This study aims to find the use of the language style used by the teacher.Design and methods: The research approach used is a qualitative approach. The research method used is content analysis.Â Â The data analysis of this research was carried out through the Miles and Huberman flow model consisting of 1) identification, 2) data reduction, 3) data presentation, 4) conclusion drawing and verification, and 5) final conclusions and recommendations.Results: third-grade teachers at SD Negeri Ciheuleut 1 in communicating with students tend to prioritize conveying messages over other things. What is meant here is close communication so that messages from the teacher will be easier and faster to be understood by students.